THE UTILIZATION OF THE COMMENT FEATURE ON INSTAGRAM ACCOUNTS IN ADVOCATING FOR LAW ENFORCEMENT IN THE CITY OF TEBING TINGGI (A STUDY ON THE INSTAGRAM ACCOUNT @TEBINGTINGGIKU) - Nyak Mutia Barokah Johan; Muhammad Alfikri Matondang (Journal Analytica Islamica, 2025)
When reflecting on the state of law enforcement in Indonesia, it becomes apparent-after reviewing various cases-that the system has not functioned effectively, and in fact, may be considered poor. The weakness of law enforcement in Indonesia is reflected in the unresolved major cases, one of which is the entrenched practice of corruption, the perpetrators of which are rarely held accountable. This reality stands in stark contrast to the treatment of cases involving ordinary citizens, where law enforcement officers are notably more responsive. As is widely known, individuals involved in corruption often belong to the upper class-officials and affluent individuals-who possess the power to interfere with the effectiveness of law enforcement itself. This study employs a qualitative approach, where data in the form of narrative descriptions or attachments are collected and then analyzed descriptively. Descriptive qualitative research is a method that describes situations and events (Nurdiansyah and Rugoyah, 2021). The data collected comprise words, images, and not numerical values. These data may originate from interview transcripts, field notes, photographs, personal documents, memos, and other official documents. These informants included Jaka, the owner of the Instagram account @tebingtinggiku, and two followers, namely @chindykhr_ and @nwanny12, who emphasized that the use of social media by the @tebingtinggiku account as a platform for public service information has had a significant impact on the law enforcement process in the City of Tebing Tinggi. This platform has been utilized optimally to ensure more effective law enforcement efforts in the region.